The Encounter of Mangupa Cultural Values and the Modern Healthcare Service Approach in Transcendental Communication - Matondang, Abdul Rahman; Rozi, Fakhrur; Samosir, Sry Lestari; Rahman, Arief (Universitas Gadjah Mada, 2025)
Mangupa is a traditional Mandailing ritual practice imbued with profound spiritual and social dimensions,serving as a form of transcendental communication that connects individuals to their community and a higher spiritual ealm. In the context of contemporary mental health services, this practice encounters complex dynamics. This study adopts a phenomenological approach to explore the subjective experiences of indigenous practitioners, mental health professionals, and patients in interpreting Mangupa as part of the psychosocial recovery process. The findings reveal that this ritual fosters therapeutic trust, provides emotional support, and offers a meaningful space for spiritual recovery. However, the integration of Mangupa into clinical settings is often constrained by administrative limitations and dominant biomedical standards. This study emphasizes the importance of fostering dialogical spaces between cultural practicesand modern medical approaches not to preserve traditional essence per se, but to generate new, ontextually dynamic meanings. Accordingly, the encounter between these two paradigms illustrates the potential for a transformative shift toward a more inclusive, participatory, and culturally grounded mental health service.